Separation membrane and method for producing same

By forming aggregated layered crystals on the membrane surface of the gas separation membrane and introducing an appropriate amount of holes, the problem of insufficient breathability and solvent resistance in the prior art is solved, and the consideration of high breathability and solvent resistance is achieved.

CN119604356APending Publication Date: 2025-03-11TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056736.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-19
Filing Date
2023-08-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high breathability and solvent resistance in gas separation membranes, and the lack of aggregated layered crystals on the surface of the membrane leads to insufficient performance.

Method used

A separation membrane with poly(4-methyl-1-pentene) as the main component is used to form aggregated layered crystals on the surface of the film, and there are holes on one side to ensure that the pore rate is between 0.1% and 10% and the average pore diameter is between 3nm and 30nm.

Benefits of technology

High breathability and better solvent resistance are achieved, ensuring that the gas separation membrane has excellent gas permeability under high differential pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604356A_ABST
    Figure CN119604356A_ABST
Patent Text Reader

Abstract

A separation membrane is used as a degassing method for removing a dissolved gas from a liquid or a gas exchange method for exchanging a dissolved gas in a liquid with a gas component in a gas phase. Provided is a separation membrane having solvent resistance while maintaining high gas permeability using poly (4-methyl-1-pentene) having excellent solvent resistance and gas permeability. In order to achieve this purpose, provided is a separation membrane comprising poly (4-methyl-1-pentene) as the main component and comprising surface layers and an inner layer, the separation membrane having layered crystals in at least one surface layer and micropores in the surface layer having the layered crystals, when the ratio of the micropores in the surface of the membrane is defined as the opening ratio and the surface of the membrane is defined as 100%, the opening ratio is 0.1-10%, and the average pore diameter of the micropores is 3-30 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas separation membrane and a method for producing the same. Background Art

[0002] As a degassing method for removing dissolved gas from a liquid or a gas exchange method for exchanging dissolved gas in a liquid with a gas component in a gas phase, there is a method using a hollow fiber membrane. For the hollow fiber membrane used, high air permeability or solvent resistance for the treated liquid is required, so poly (4-methyl-1-pentene) with excellent characteristics is sometimes used as a membrane material. In the hollow fiber membrane, a membrane with a dense surface layer on the surface can inhibit the solvent from invading the membrane interior of the hollow fiber membrane, so it is preferred in terms of improving solvent resistance.

[0003] So far, various methods have been proposed to obtain a breathable membrane using polyolefin polymers as materials. For example, Patent Document 1 discloses a wet method using polyolefin polymers. The membrane of Patent Document 1 is a polymer solution obtained by dissolving a polyolefin polymer in a good solvent and extruding it from a die at a temperature higher than the melting point of the polyolefin resin, and contacting the polymer solution with a cooling solvent. The polyolefin polymer forms a dense non-porous substance on the surface of the membrane through heat-induced phase separation, and becomes a porous integrated asymmetric structure formed inside the membrane. The method of Patent Document 1 has insufficient solvent resistance.

[0004] Patent document 2 discloses a melt spinning method using a polyolefin polymer. Specifically, a multi-cylindrical spinning nozzle is used to configure a crystalline thermoplastic polymer and a second polymer into two layers for melt composite spinning, followed by stretching to make only the layer containing the crystalline thermoplastic polymer porous. That is, a polyolefin resin is extruded from a die at a temperature above the melting point and cooled and solidified, followed by stretching, thereby partially opening the inside to form a structure with a non-porous surface and a porous inside. Although the method of patent document 2 can obtain a film with high strength, the air permeability and solvent resistance are insufficient.

[0005] Patent document 3 discloses a melt spinning method for obtaining a hollow fiber microporous membrane. Specifically, a polyolefin resin is extruded from a die at a temperature above the melting point and cooled and solidified, and stretched after a long heat treatment, thereby cracking the interface of the layered crystals, thereby forming a connected microporous structure. Although the method of patent document 3 can obtain a membrane with high air permeability, a dense surface layer is not formed on the membrane surface, so the solvent cannot be inhibited from invading the interior of the hollow fiber membrane, and due to the cracking of the interface of the layered crystals, the solvent resistance is insufficient.

[0006] Patent Document 4 discloses a melt spinning method for obtaining a hollow fiber heterogeneous membrane. Heterogeneity refers to the process of melt-extruding a highly crystalline polyolefin polymer under a certain pulling tension, followed by air cooling and stretching, thereby forming a structure with no pores on the surface and micropores in the inner layer. The method of Patent Document 4 can provide micropores on the membrane surface by controlling the pulling tension, but the air permeability is low and the solvent resistance is insufficient.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2000 / 043113

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 7-116483

[0011] Patent Document 3: Japanese Patent No. 5413317

[0012] Patent Document 4: Japanese Patent Application Laid-Open No. 6-210146 Summary of the invention

[0013] Problems to be solved by the invention

[0014] According to the findings of the present inventors, in a method for separating dissolved gas from a liquid or a gas exchange method for exchanging dissolved gas in a liquid with gas components in a gas phase, for high solvent resistance, it is not sufficient for the membrane surface to be dense alone, and it is important for the layered crystals to grow densely and sufficiently to form a membrane surface with aggregated layered crystals.

[0015] The membranes obtained by the methods of Patent Documents 1 and 4 have a problem that the surface is dense but no lamellar crystals are formed, and the solvent resistance is insufficient. In addition, although the separation membrane obtained in Patent Document 2 has high strength, the porosity is insufficient, so it does not have sufficient air permeability, and further, sufficient lamellar crystals are not formed on the membrane surface, so the solvent resistance is also insufficient. In addition, although the separation membrane obtained in Patent Document 3 has high air permeability, it does not have a dense surface layer on the membrane surface, and although lamellar crystals are visible on the membrane surface, it does not have aggregated lamellar crystals, so the solvent resistance is insufficient.

[0016] Thus, poly(4-methyl-1-pentene) is a material with excellent solvent resistance, but the prior art does not have aggregated lamellar crystals on the membrane surface, and cannot take into account both air permeability and solvent resistance. On the other hand, in order to achieve high solvent resistance, the membrane surface with aggregated lamellar crystals is covered by plate-like crystals, so there is a problem that gas is shielded and air permeability is easily deteriorated.

[0017] In summary, the problem to be solved by the present invention is to provide a separation membrane having both air permeability and better solvent resistance using poly(4-methyl-1-pentene).

[0018] Means for solving problems

[0019] The present inventors conducted intensive research to solve the above-mentioned problems and found that the following separation membrane has both high air permeability and solvent resistance, wherein the separation membrane is a membrane with poly (4-methyl-1-pentene) as the main component, wherein the membrane surface has aggregated layered crystals, and the membrane surface on the side with the aggregated layered crystals has openings, and the openings have selective air permeability, thereby completing the present invention. The separation membrane of the present invention has the following structure.

[0020] 1. A separation membrane having poly(4-methyl-1-pentene) as a main component and comprising a surface layer and an inner layer, wherein at least one surface layer has layered crystals, and the surface layer having the layered crystals has micropores, and when the proportion of the micropores in the membrane surface is set as the opening rate and the membrane surface is set as 100%, the opening rate is 0.1% to 10%, and the average pore size of the micropores is 3nm to 30nm.

[0021] 2. The separation membrane according to item 1, wherein the N 2 The performance is above 1000 GPU.

[0022] 3. The separation membrane according to 1 or 2, wherein the crystallinity of the membrane surface having the surface layer of the lamellar crystals is 5% to 35%.

[0023] 4. The separation membrane according to any one of 1 to 3, wherein the area ratio of the lamellar crystals on the membrane surface having the surface layer of the lamellar crystals is 10% to 60% when the area of ​​the membrane surface excluding the openings is 100%.

[0024] 5. The separation membrane according to any one of 1 to 4, wherein a period of the lamellar crystals on the membrane surface having the surface layer of the lamellar crystals is 10 nm to 80 nm.

[0025] 6. The separation membrane according to any one of 1 to 5, wherein in the surface layer having the lamellar crystals, the number of micropores is 1 / μm 2 Above and 20000 / μm 2 the following.

[0026] 7. The separation membrane according to any one of 1 to 6, wherein the porosity of the separation membrane is 30% to 70%.

[0027] 8. The separation membrane according to any one of 1 to 7, wherein the inner layer of the separation membrane has a porosity of 25% to 60% when the cross-sectional area when cut in the thickness direction is set to 100%.

[0028] 9. The separation membrane according to any one of 1 to 8, wherein the separation membrane is in a hollow fiber shape.

[0029] 10. The separation membrane according to 9, wherein the surface layer having the layered crystals is an outer surface of a separation membrane in a hollow fiber shape.

[0030] 11. The separation membrane according to 9 or 10, wherein in a cross section of the inner layer of the hollow fiber-shaped separation membrane cut parallel to and along the thickness direction of the membrane, a ratio a / b of a major axis length a to a minor axis length b of the pores is 1.0 to 5.0.

[0031] 12. The separation membrane according to any one of 1 to 9, wherein after the separation membrane is immersed in the following organic solvent A for 3 seconds, the N 2 Through performance of 5 GPU or above,

[0032] Organic solvent A: chloroform / isopropanol = 1 / 1 (volume / volume).

[0033] 13. A degassing module comprising the separation membrane according to any one of 1 to 12.

[0034] 14. A method for producing a separation membrane, comprising the steps (A1) to (A2) below:

[0035] (A1) a preparation step of melt-kneading a mixture containing 10% to 50% by mass of poly(4-methyl-1-pentene) and 50% to 90% by mass of a plasticizer to obtain a resin composition;

[0036] (A2) Molding process: The resin composition is discharged from a discharge die, passed through an idle run of 10 mm to 30 mm, and immediately introduced into a cooling bath of a solvent having a solubility parameter distance Ra of 4.0 to 14.0 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 3.0 to 6.0 relative to the plasticizer, to obtain a resin molded product.

[0037] 15. A method for manufacturing a separation membrane according to 14, wherein, after the molding step (A2) of obtaining a resin molded product, it further includes a cleaning step (A3), in which the resin molded product is treated with a solvent having a solubility parameter distance Ra in the range of 8 to 35 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb in the range of 5 to 35 relative to the plasticizer, and the plasticizer contained in the resin molded product is extracted into the solvent.

[0038] 16. The method for producing a separation membrane according to 15, wherein in the (A3) washing step, the resin molded product is stretched to 1.1 to 5.0 times.

[0039] 17. A method for producing a separation membrane, comprising the steps (B1) to (B3) described below, wherein in the washing step of step (B3), the resin molded article is stretched to 1.1 to 5.0 times,

[0040] (B1) a preparation step of melt-kneading a mixture containing 10% to 50% by mass of poly(4-methyl-1-pentene) and 50% to 90% by mass of a plasticizer to obtain a resin composition;

[0041] (B2) a molding step of immediately introducing the resin composition into a cooling bath of a solvent having a solubility parameter distance Ra of 5.0 to 18.0 with respect to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 1.0 to 2.9 or 6.5 to 10.0 with respect to the plasticizer after the resin composition is discharged from the discharge port die, to obtain a resin molded product;

[0042] (B3) Cleaning step: The obtained resin molded product is treated with a solvent having a solubility parameter distance Ra of 8 to 35 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 5 to 35 relative to the plasticizer, thereby extracting the plasticizer contained in the resin molded product into the solvent.

[0043] Effects of the Invention

[0044] According to the present invention, a separation membrane having high air permeability is provided by providing aggregated lamellar crystals on the surface of the membrane layer and having openings, i.e., micropores, which do not adversely affect solvent resistance. That is, by using poly(4-methyl-1-pentene), an excellent separation membrane having both high air permeability and better solvent resistance is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 : is a schematic diagram schematically showing the membrane surface of a hollow fiber-shaped separation membrane.

[0046] Figure 2 : This is an example of a SEM image of the membrane surface of the separation membrane photographed at a magnification of 60,000 times.

[0047] Figure 3 : This is an example of a SEM image obtained by photographing a cross section of the separation membrane cut along the thickness direction at a magnification of 10,000 times.

[0048] Figure 4 :It is Figure 3 The processed image of the surface cross section is obtained by removing noise after binarization of the image.

[0049] Figure 5 :It is used by Figure 4 The image is processed to determine the thickness of the surface layer.

[0050] Figure 6 : It is an explanatory diagram about the method of measuring the major axis length a and the minor axis length b of the pores in the inner layer of the separation membrane. DETAILED DESCRIPTION

[0051] The separation membrane of the present invention is characterized in that it has poly (4-methyl-1-pentene) as a main component, has aggregated layered crystals in at least one dense surface layer, has openings on the membrane surface of the aforementioned surface layer having the aforementioned aggregated layered crystals, and when the aforementioned membrane surface is set to 100%, the porosity is 0.1% to 10%, and the average pore size of the openings is 3 to 30 nm. Here, the porosity refers to the proportion of the total area of ​​micropores in the area of ​​the membrane surface. In this specification, the ratio (percentage, part, etc.) based on mass is the same as the ratio (percentage, part, etc.) based on weight. Below, the separation membrane of the present invention is described.

[0052] (Resin composition constituting separation membrane)

[0053] The resin composition constituting the separation membrane of the present invention contains poly(4-methyl-1-pentene) as a main component as shown in (1) below. In addition to (1), it may contain the components shown in (2) to (3) below.

[0054] (1) Poly(4-methyl-1-pentene) (hereinafter referred to as "PMP")

[0055] The separation membrane of the present invention needs to contain PMP as a main component. The main component here refers to a component that contains 70% by mass or more of all the components of the separation membrane.

[0056] PMP only needs to have repeating units derived from 4-methyl-1-pentene. PMP may be a homopolymer of 4-methyl-1-pentene, or a copolymer with a monomer other than 4-methyl-1-pentene that is copolymerizable with 4-methyl-1-pentene. Specific examples of monomers copolymerizable with 4-methyl-1-pentene include olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene (hereinafter referred to as "olefins having 2 to 20 carbon atoms").

[0057] Examples of the olefin having 2 to 20 carbon atoms copolymerized with 4-methyl-1-pentene include ethylene, propylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. The olefin having 2 to 20 carbon atoms copolymerized with 4-methyl-1-pentene may be one kind or a combination of two or more kinds.

[0058] The density of the PMP raw material used as the raw material of the separation membrane of the present invention is preferably 825 to 840 (kg / m 3 ), more preferably 830 to 835 (kg / m 3 When the density is less than the above range, the mechanical strength of the separation membrane may be reduced, defects may occur, etc. On the other hand, when the density is greater than the above range, the air permeability tends to be reduced.

[0059] The melt flow rate (MFR) of PMP is not particularly specified as long as it is easy to mix with the plasticizer described later and can be co-extruded. Under the conditions of temperature 260°C and 5kg load, it is preferably 1 to 200g / 10min, more preferably 5 to 30g / 10min. If the MFR is within the above range, it is easy to extrude into a relatively uniform film thickness. The PMP raw material can be a commercially available PMP polymer, such as TPX (registered trademark) manufactured by Mitsui Chemicals, Inc.

[0060] The content of PMP in the separation membrane is preferably 70 to 100 mass %, more preferably 80 to 100 mass %, and further preferably 90 to 100 mass %, when all components of the separation membrane are 100 mass %. When the content of PMP in the separation membrane is 70 mass % or more, air permeability becomes sufficient.

[0061] In addition, the content of PMP in the raw material for manufacturing the separation membrane is preferably 10% to 50% by mass when the total amount of the components constituting the raw material is set to 100% by mass. The membrane strength of the separation membrane becomes good when the content is 10% by mass or more. On the other hand, the permeability of the separation membrane becomes good when the content is 50% by mass or less. The content is more preferably 15 to 50% by mass, further preferably 20 to 45% by mass, and particularly preferably 25 to 40% by mass.

[0062] (2) Plasticizer

[0063] The resin composition constituting the separation membrane of the present invention may contain a plasticizer for PMP. From the viewpoint of improving permeability, the content of the plasticizer in the separation membrane is preferably 1000 ppm (mass basis), more preferably 500 ppm (mass basis) or less, and particularly preferably 100 ppm (mass basis) or less.

[0064] The plasticizer of PMP is not particularly limited as long as it is a compound that can thermoplasticize PMP. As the plasticizer of PMP, not only one plasticizer can be used, but also two or more plasticizers can be used in combination. As the plasticizer of PMP, for example, palm kernel oil, dibutyl phthalate, dioctyl phthalate, butyl stearate, dibenzyl ether, coconut oil or a mixture thereof can be cited. Among them, from the viewpoint of compatibility and wire drawing properties, dibutyl phthalate and dibenzyl ether are preferably used.

[0065] The plasticizer of PMP is preferably dissolved from the separation membrane after forming the separation membrane. In addition, the content of the plasticizer in the raw material for manufacturing the separation membrane is preferably 50% to 90% by mass when the entirety of the components constituting the raw material is set to 100% by mass. The membrane strength of the separation membrane becomes good when the content in the raw material is 90% by mass or less. In addition, the permeability of the separation membrane becomes good when the content in the raw material is 50% by mass or more. The content in the raw material is more preferably 50% to 85% by mass, further preferably 55% to 80% by mass, and particularly preferably 60 to 75% by mass.

[0066] (3) Additives

[0067] The resin composition constituting the separation membrane of the present invention may further contain additives other than those described in (2) within a range not impairing the effects of the present invention.

[0068] Examples of the additives include resins such as cellulose ether, polyacrylonitrile, polyolefin, polyvinyl compound, polycarbonate, poly(meth)acrylate, polysulfone or polyethersulfone, organic lubricant, crystal nucleating agent, organic particles, inorganic particles, end-capping agent, chain extender, ultraviolet absorber, infrared absorber, anti-coloring agent, matting agent, antibacterial agent, antistatic agent, deodorant, flame retardant, weathering agent, antistatic agent, antioxidant, ion exchanger, defoaming agent, coloring pigment, fluorescent brightener or dye, etc.

[0069] (Shape of separation membrane)

[0070] The separation membrane of the present invention preferably has a hollow fiber shape (hereinafter, sometimes referred to as a "hollow fiber membrane"), but the separation membrane of the present invention is not limited to the hollow fiber shape. The hollow fiber membrane can be efficiently filled into the module and can increase the effective membrane area per unit volume of the module, so it is preferred.

[0071] The shape of the separation membrane in the present invention, that is, the thickness of the separation membrane, the outer diameter and inner diameter when the separation membrane is a hollow fiber membrane, and the hollowness ratio can be observed by, for example, applying stress to the separation membrane that has been sufficiently cooled in liquid nitrogen, cutting it in the thickness direction of the membrane, and observing the obtained cross section (hereinafter referred to as "diameter cross section") using an optical microscope or a scanning electron microscope (SEM). The specific method is described in detail in the Examples.

[0072] The separation membrane of the present invention is composed of a dense surface layer and a porous inner layer. It should be noted that the separation membrane obtained by the method of Patent Document 3 is a microporous membrane having a microporous structure formed on the entire membrane by stretching, which is different from the separation membrane of the present application. From the viewpoint of taking into account both permeability and membrane strength, the thickness of the separation membrane as a whole, which combines the surface layer and the inner layer, is preferably 10 μm to 500 μm. The thickness of the separation membrane as a whole is preferably 30 μm or more, more preferably 50 μm or more. In addition, the thickness is more preferably 200 μm or less, more preferably 150 μm or less, and particularly preferably 100 μm or less.

[0073] From the viewpoint of taking into account both the effective membrane area and the membrane strength when filling the module, the outer diameter of the hollow fiber membrane is preferably 50 μm to 2500 μm. The outer diameter of the hollow fiber membrane is more preferably 100 μm or more, further preferably 200 μm or more, and particularly preferably 300 μm or more. In addition, the outer diameter is more preferably 1000 μm or less, further preferably 500 μm or less, and particularly preferably 450 μm or less.

[0074] In addition, from the relationship between the pressure loss of the fluid flowing in the hollow part and the buckling pressure (seat buckling pressure), the inner diameter of the hollow fiber membrane is preferably 20 μm to 1000 μm. The inner diameter of the hollow fiber membrane is more preferably 50 μm or more, further preferably 100 μm or more, and particularly preferably 150 μm or more. In addition, the inner diameter is more preferably 500 μm or less, further preferably 300 μm or less, and particularly preferably 250 μm or less.

[0075] In addition, from the relationship between the pressure loss of the fluid flowing in the hollow part and the buckling pressure, the hollowness of the hollow fiber membrane is preferably 15% to 70%. The hollowness is more preferably 20% or more, and further preferably 25% or more. In addition, the hollowness is more preferably 60% or less, further preferably 50% or less, and particularly preferably 40% or less.

[0076] There is no particular limitation on the method for making the outer diameter, inner diameter and hollow ratio of the hollow fibers in the hollow fiber membrane within the above ranges. For example, the method can be adjusted by appropriately changing the draft ratio, which can be calculated by the shape of the discharge hole of the spinning die for manufacturing the hollow fibers or the winding speed / discharge speed.

[0077] (Observation of membrane surface)

[0078] The separation membrane of this embodiment has aggregated layered crystals in at least one surface layer, and has openings on the membrane surface between the layered crystals for selectively transmitting gas. It should be noted that the surface of the surface layer is referred to as the membrane surface, which is manifested as an opening in a two-dimensional membrane surface and as micropores in a surface layer having thickness. Figure 1 This is a schematic diagram (enlarged view) schematically showing the membrane surface of a separation membrane in a hollow fiber shape. In the hollow fiber membrane 8, the membrane surface 1 having aggregated layered crystals may be located on the outer surface side of the hollow structure, on the inner surface side, or on both the outer surface and the inner surface.

[0079] Aggregated lamellar crystals 6 refer to a portion where the proportion of lamellar crystals 6 is 10% or more when the membrane surface 1 of the separation membrane is observed using a scanning electron microscope (hereinafter referred to as "SEM") at a magnification of 60,000 times, with the surface area excluding micropores, i.e., openings 2, being 10% or more. Lamellar crystals 6 refer to stripe-like convex portions, i.e., stripe-like bright portions, in an image of the surface of the separation membrane observed using the SEM at a magnification of 60,000 times. Openings 2 refer to concave portions with a diameter of 1 nm to 10 μm when the membrane surface 1 of the separation membrane is observed using the SEM at a magnification of 60,000 times.

[0080] An example of an image of the membrane surface 1 of the separation membrane photographed with a SEM at a magnification of 60,000 times is shown in FIG. Figure 2 . Figure 2 In the present invention, the layered crystals 6 are densely aggregated with a plurality of crystal chains, and the layered crystals are adjacently formed and aggregated. The openings 2 exist in the aggregated layered crystals.

[0081] The proportion of the lamellar crystals in the area of ​​the membrane surface excluding the openings can be obtained by observing the membrane surface using SEM, and calculating the area ratio of the lamellar crystals 6 and the area ratio of the openings 2 in the entire observed image, i.e., the porosity, from the obtained image. The micropores of 1 nm or more in the membrane surface, i.e., the openings 2, can be obtained by observing the surface 1 of the separation membrane using SEM, and extracting only the pores with a diameter greater than 1 nm after binarizing the obtained image in the image analysis software "ImageJ". The specific calculation method is described in detail in the examples.

[0082] like Figure 2As shown, the separation membrane of this embodiment has striped layered crystals growing on the membrane surface 1. Layered crystals are structures in which the molecular chains of PMP are folded into plates and aggregated, and exhibit excellent solvent resistance. Figure 2 In the embodiment of the present invention, the striped layer crystals shown in the bright part are observed as convex parts, forming a layer structure in which several layer crystal groups are closely gathered. On the other hand, between the layer crystals and the layer crystals, there is an opening portion 2, i.e., micropores, having an average pore size of more than 3nm and less than 30nm. The opening portion selectively permeates gas, thus becoming a separation membrane having a membrane surface with both high gas permeability and solvent resistance. The surface layer and membrane surface 1 with aggregated layer crystals are preferably an outer surface when the separation membrane is a hollow fiber shape.

[0083] (Layered crystals on the membrane surface)

[0084] It is important for the separation membrane of the present invention that, in the membrane surface 1 having aggregated lamellar crystals, the proportion of lamellar crystals in the total area of ​​the membrane surface excluding the openings 2 is 10% to 60%. It is preferred that the proportion of lamellar crystals is 10% or more in order to obtain high solvent resistance, and it is preferred that the proportion of lamellar crystals is 60% or less in order to improve the air permeability outside the openings. The proportion of lamellar crystals is more preferably 20% to 60%, further preferably 25% to 55%, and particularly preferably 30% to 40%.

[0085] In addition, the period of the lamellar crystals in the membrane surface 1 of the present invention is preferably 10nm to 80nm. The period of the lamellar crystals refers to the distance from the striped convex portion to the nearest striped convex portion in the image of the surface of the separation membrane observed using SEM at a magnification of 30,000 times. There is a tendency that the smaller the period of the lamellar crystals, the higher the aggregation of the lamellar crystals. When the period of the lamellar crystals is more than 10nm, the solvent resistance becomes good, so it is preferred. When the period of the lamellar crystals is less than 80nm, the air permeability outside the open pores becomes good, so it is preferred. The period of the lamellar crystals is more preferably 20nm to 50nm, further preferably 25nm to 45nm, and particularly preferably 30nm to 45nm. The specific determination method of the period of the lamellar crystals is described in detail in the examples.

[0086] (Crystallinity of film surface)

[0087] The separation membrane of the present invention preferably has a crystallinity of 5% to 35% in the membrane surface 1. In the present invention, the thickness of the membrane surface 1 is very small, so the crystallinity of the membrane surface 1 is consistent with the crystallinity of the surface layer 3. When the crystallinity of the membrane surface 1 is 5% or more, the solvent resistance becomes good, and when it is 35% or less, the permeability outside the opening portion becomes good. The crystallinity in the membrane surface 1 refers to the value obtained by infrared spectroscopy (hereinafter sometimes shown as "IR"), and the specific measurement method is described in the examples. The crystallinity in the membrane surface 1 is more preferably 15% to 35%, further preferably 20% to 35%, and particularly preferably 30% to 35%.

[0088] (Openings on the membrane surface)

[0089] It is important for the separation membrane of the present invention that the average pore diameter of the openings 2, ie, micropores, in the membrane surface 1 is 3 nm to 30 nm. Figure 1 and Figure 2 In the figure, the openings 2 on the membrane surface shown in the dark part exist without hindering the characteristics of each layered crystal 6 of the aggregated layered crystals 6. The average pore size of the openings in the membrane surface 1 is preferably 3 nm or more, which is preferred in terms of obtaining high air permeability, and is 30 nm or less, so that the solvent resistance becomes good. The average pore size of the openings 2, i.e., micropores in the membrane surface 1 is more preferably 3 to 20 nm, further preferably 3 to 18 nm, and particularly preferably 3 nm to 16 nm. The specific calculation method of the average pore size is described in detail in the examples.

[0090] In addition, it is important that the porosity in the membrane surface 1 is 0.1% to 10%. The porosity is the ratio of the total area of ​​the microporous part to the area of ​​the membrane surface, expressed as a ratio when the area of ​​the projected membrane surface is set to 100%. That is, the porosity refers to the area ratio of the open part to the entire observed image when the surface of the hollow fiber membrane is observed using SEM at a magnification of 60,000 times. It is preferred to obtain high air permeability by having a porosity of 0.1% or more in the membrane surface 1, and solvent resistance becomes good by being 10% or less. The porosity in the membrane surface 1 is more preferably 0.2% to 5.0%, further preferably 0.5% to 2.0%, and particularly preferably 1.0% to 1.5%. The specific calculation method of the porosity is described in detail in the examples.

[0091] Furthermore, the number of openings 2 in the film surface 1 is preferably 1.0 / μm. 2 ~20000 / μm 2 The number of openings is 1.0 / μm 2 Above, it is preferred to obtain high air permeability, and 20000 pieces / μm 2 The number of openings is more preferably 10 / μm. 2 ~10000 / μm2 , more preferably 50 / μm 2 ~5000 / μm 2 , particularly preferably 100 μm 2 ~2000 / μm 2 The specific calculation method of the number of openings per constant area is described in detail in the examples.

[0092] In addition, in the film surface 1, the opening ratio (%) is divided by the number of openings 2 per constant area (number / μm 2 ) is preferably 0.1 (%·μm 2 D is an index of the area occupied by each opening 1, i.e., the size of each opening 1. When D is 0.1 or less, the intrusion of the solvent into the interior of the film is suppressed, and the solvent resistance becomes good. D is more preferably 0.05 or less, further preferably 0.03 or less, and particularly preferably 0.01 or less.

[0093] In the separation membrane of the present invention, the layered crystals on the membrane surface 1 are in an aggregated state with an area ratio of 10% to 60% and a period of 10 nm to 80 nm. Furthermore, the crystallinity of the surface is 5% to 35%, which is preferred from the viewpoint of obtaining higher solvent resistance. On the other hand, in order to achieve high solvent resistance, the membrane surface with aggregated layered crystals is covered with plate-like crystals, so the gas is shielded and the air permeability is easily deteriorated. The separation membrane of the present invention has 1 / μm between the layered crystals and the layered crystals. 2 The openings 2 have an average pore size of 3 nm or more and 30 nm or less, and the openings 2 exhibit air permeability. However, if the area occupied by the openings 2 exceeds 20,000 / μm 2 In summary, the separation membrane of the present invention has aggregated layered crystals on the surface layer, and has micropores on the membrane surface, the average pore size of the micropores is 3nm to 30nm, the porosity is 0.1% to 10%, and the number of pores on the membrane surface is 1 / μm. 2 As described above, a membrane surface having both high air permeability and solvent resistance is formed.

[0094] (Observation of membrane cross section)

[0095] The separation membrane of this embodiment has a dense layer on the surface layer 3 on the side where the membrane surface 1 exists. Figure 3As shown, the separation membrane has a surface layer 3 and an inner layer 4 thereunder. The surface layer 3 refers to the portion until a straight line perpendicular to the surface is drawn from any point on the surface of the separation membrane to the other surface side (inner layer side) at a magnification of 10,000 times when observing a cross section of the separation membrane cut along the thickness direction using a scanning electron microscope (SEM) until the straight line first reaches a hole exceeding 50 nm. The inner layer 4 is a layer located below the surface layer 3. That is, the surface layer 3 has no holes exceeding 50 nm and is a denser layer than the inner layer.

[0096] The thickness of the surface layer 3 can be obtained as follows, for example, by applying stress to the separation membrane that has been sufficiently cooled in liquid nitrogen (using a razor or a microtome or a wide ion beam as needed), observing a cross section perpendicular to the length direction of the separation membrane and parallel to the thickness direction of the membrane (hereinafter referred to as a "cross section") or a cross section parallel to the length direction of the separation membrane and parallel to the thickness direction of the membrane (hereinafter referred to as a "longitudinal section") using a scanning electron microscope (SEM), binarizing the resulting image using the image analysis software "ImageJ", extracting only pores larger than 50 nm, drawing a straight line perpendicularly from the membrane surface 1, and measuring the distance to the pore.

[0097] It should be noted that the cross section of the hollow fiber membrane has the same meaning as the radial cross section. In addition, the length direction of the hollow fiber membrane refers to the direction perpendicular to the width direction of the hollow fiber membrane. In addition, the width direction of the hollow fiber membrane refers to the direction parallel to the radial direction of the hollow fiber membrane. The width direction can be expressed in other words as the direction parallel to the hollow surface, that is, the in-plane direction of the hollow surface. Therefore, the length direction of the hollow fiber membrane can be expressed in other words as the direction perpendicular to the hollow surface. The thickness of the surface layer refers to the length, in the above-mentioned SEM image, from any point on the membrane surface of the separation membrane to the inner layer side when a straight line perpendicular to the outer surface is drawn until the first hole exceeding 50nm is reached. The specific measurement method is described in detail in the embodiments.

[0098] In addition, the separation membrane of the present invention is a porous membrane having voids in the inner layer 4. When the separation membrane of the present embodiment is observed in a radial section or a longitudinal section at a magnification of 2,000 times using SEM, it is preferred that there are 3 or less voids greater than 10 μm per field of view. The voids greater than 10 μm are mostly present in the inner layer 4. A void refers to a concave portion with a diameter of 10 nm or more when the radial section or longitudinal section of the separation membrane is observed at a magnification of 2,000 times using SEM. A depression refers to a hole, which is represented by the diameter size of a sphere. The strength of the separation membrane is improved by having 3 or less voids greater than 10 μm in the membrane cross section. The voids of 10 μm or more in the membrane cross section can be obtained by observing the cross section or longitudinal section of the separation membrane using SEM at a magnification of 2,000 times, and binarizing the obtained image in the image analysis software "ImageJ" to extract only the pores with an average diameter greater than 10 μm.

[0099] The number of voids larger than 10 μm in the film cross section is more preferably 2 or less, further preferably 1 or less, and particularly preferably 0. The method for measuring voids larger than 10 μm in the film cross section is described in detail in the Examples.

[0100] The inner layer of the separation membrane of the present embodiment preferably has an average pore size of 100nm to 1000nm in the voids when the membrane cross section is observed using SEM. The average pore size of the voids in the membrane cross section can be obtained by observing the cross section or longitudinal section of the separation membrane using SEM at a magnification of 10,000 times, and binarizing the resulting image in the image analysis software "ImageJ", extracting pores with an average diameter greater than 10nm. When the average pore size of the membrane cross section is 100nm or more, the permeability becomes good, and when it is 1000nm or less, the strength of the separation membrane becomes good. The average pore size of the voids in the membrane cross section is preferably 100nm to 800nm, more preferably 100 to 600nm, further preferably 100nm to 570nm, and particularly preferably 100 to 500nm.

[0101] The above-mentioned voids can have any geometric shape, for example, they can have an elongated, cylindrical, circular shape or an irregular shape of varying degrees. The shape of the pores can be evaluated by using a slicer to cut the separation membrane that is fully cooled in liquid nitrogen, using SEM to observe the exposed cross section, and obtaining the ratio a / b of the major axis length a and the minor axis length b of the pores. It should be noted that when the separation membrane is in the shape of a flat membrane, it is cut in the direction where the Young's modulus is the largest and parallel to the thickness direction of the membrane. When the separation membrane is in the shape of a hollow fiber, the direction where the Young's modulus is the largest is the direction parallel to the length direction of the membrane, and the longitudinal section of the hollow fiber membrane is observed. The specific determination method of a / b is described in detail in the embodiments.

[0102] In the separation membrane of the present embodiment, when the separation membrane is stretched, both the surface layer and the inner layer are stretched. When stretched, the length a of the major axis is also likely to become larger. It should be noted that the ratio of a / b can be easily adjusted by balancing the resin extrusion speed and the pulling tension, or by stretching. For example, in order to adjust the ratio of a / b to be larger, it can be easily adjusted by reducing the resin extrusion speed, increasing the pulling tension, and increasing the stretching ratio. In the separation membrane of the present embodiment, a / b is related to the porosity and average pore size of the aforementioned membrane surface.

[0103] In the separation membrane of the present embodiment, the direction of the major axis length a of the pores tends to be parallel to the direction in which the Young's modulus is the largest. That is, the direction of the major axis length a of the pores is roughly parallel to the direction in which the Young's modulus is the largest and the length direction of the membrane when the separation membrane is in the shape of a hollow fiber. In the separation membrane of the present embodiment, a / b is preferably 1.0 to 5.0. By a / b being 5.0 or less, the average pore size, porosity, and number of pores on the aforementioned membrane surface are in the preferred range, forming a membrane surface that takes into account both high air permeability and solvent resistance. a / b is more preferably 1.5 to 4.0, further preferably 2.0 to 3.5, and particularly preferably 2.5 to 3.0.

[0104] In addition, the separation membrane of the present embodiment preferably has a porosity of 25% to 60% when the membrane cross section is observed using SEM. Porosity is the proportion of the pore portion in the membrane cross section, expressed as the proportion of the pores when the area of ​​the projected membrane cross section is set to 100%. That is, it refers to the area ratio of the pore portion as a void in the entire observed image when the membrane cross section of the separation membrane is observed using SEM at a magnification of 10,000 times. It is preferred to have a porosity of 25% or more in the membrane cross section from the perspective of obtaining high air permeability, and the membrane strength becomes good when it is 60% or less. The porosity in the membrane cross section is more preferably 30 to 55%, further preferably 35 to 50%, and particularly preferably 40 to 50%. The specific calculation method of the porosity of the membrane cross section is described in detail in the examples.

[0105] (Porosity)

[0106] The separation membrane of the present invention has a porosity of 30% or more and 70% or less as a whole. When the porosity is 30% or more, the permeability becomes good, and when it is 70% or less, the membrane strength becomes good. The porosity is preferably 40% or more and 65% or less, more preferably 45% or more and 60% or less, and particularly preferably 53% or more and 60% or less. In order to obtain a porosity in this range, it is preferred to use a structure formed by heat-induced phase separation described later. It should be noted that the porosity of the present application refers to the porosity of the separation membrane as a whole including the surface layer and the inner layer, and the specific method for measuring the porosity is described in detail in the examples.

[0107] (Breathability)

[0108] The separation membrane of the present invention is preferably N at 100 kPa and 37°C. 2 The performance is above 1000 GPU. 2 The transmittance is more preferably 3000 GPU or more, and further preferably 50000 GPU or more. The calculation method is described in detail through the examples.

[0109] (Separation coefficient α(CO 2 / N 2 ))

[0110] The separation membrane of the present invention has layered crystals and openings on the membrane surface, thereby having both solvent resistance and high gas permeability, and due to the pore size of the opening, the permeation of gas is mainly carried out by "Knudsen diffusion". On the other hand, in a non-porous structure, since there are no through holes, the gas permeability is reduced, but the permeation of gas is carried out by a dissolution-diffusion mechanism. That is, the density of the membrane surface can be evaluated by the separation coefficient of the gas, and there is a tendency for the efficiency of degassing and gas exchange to decrease in a high-density membrane.

[0111] Generally, the permeation in a polymer membrane depends on the pore size in the membrane. In a porous membrane having pores of 3 nm to 10 μm in size, gas permeates mainly by “Knudsen diffusion”. In this case, the separation coefficient α, which represents the ratio of the permeation coefficient P of two gases or the permeation flow rate Q of the gases, is obtained by the square root of the ratio of the molecular weights of the gases. Therefore, for example, with CO 2 and N 2 The relevant separation factor α(CO 2 / N 2 ) is √28 / √44=0.80.

[0112] On the other hand, in a membrane having pores with a maximum diameter of 3 nm, gas permeates by a dissolution-diffusion mechanism. In this case, the separation coefficient α depends only on the polymer material and not on the membrane thickness. Therefore, α(CO 2 / N 2 ) can be expressed as P(CO 2 ) / P(N 2 ) or Q(CO 2 ) / Q(N 2 In the commonly used polymers, at least one α(CO 2 / N 2 ) value. If it is a dissolution-diffusion mechanism, the gas permeability will decrease, so α(CO 2 / N 2 ) is 1 or less, since the efficiency of degassing and gas exchange becomes good, it is preferred.

[0113] When a gas passes through a non-porous membrane, the gas permeability coefficient decreases, while the gas separation coefficient increases. Therefore, the pore diameter that controls the gas permeability of the membrane of the present invention can be determined by targeting CO 2 and N 2 The gas separation factor α(CO 2 / N 2 ) to read. Gas separation factor α(CO 2 / N 2) is greater than 1.0, the membrane has a non-porous structure. When the separation membrane has a non-porous structure, the efficiency of degassing and gas exchange is reduced, so it is not suitable for use. In contrast, the gas separation coefficient α(CO 2 / N 2 ) is 1.0 or less, the membrane has high degassing or gas exchange performance. Therefore, the gas separation coefficient α(CO 2 / N 2 ) is preferably 0.8 to 1.0.

[0114] (Air permeability after organic solvent immersion)

[0115] The separation membrane of the present invention is preferably immersed in chloroform / isopropanol = 1 / 1 (volume / volume) for 3 seconds and then the pressure difference is 100 kPa and N at 37°C. 2 The permeability X is 5 GPU or more. When the value of X is 5 GPU or more, the solvent resistance becomes good. The value of X is more preferably 10 GPU or more, further preferably 200 GPU or more, and particularly preferably 400 GPU or more.

[0116] (Method for producing separation membrane)

[0117] The separation membrane of the present invention can be produced by the following method A or method B. For each step of method A and method B, in the case of method A, there are the following steps (A1) to (A2), preferably steps (A1) to (A3), and in the case of method B, there are the following steps (B1) to (B3). Each step is as follows.

[0118] <Method A>

[0119] (A1): Preparation process

[0120] (A2): Forming process

[0121] (A3): Cleaning process

[0122] Method B

[0123] (B1): Preparation process

[0124] (B2): Forming process

[0125] (B3): Cleaning process

[0126] Hereinafter, each step of method A will be described.

[0127] (A1) Preparation process

[0128] This is a preparation step of melt-kneading a mixture containing 10 to 50% by mass of poly(4-methyl-1-pentene) and 50 to 90% by mass of a plasticizer to obtain a resin composition.

[0129] In the preparation process of obtaining the resin composition, a mixture containing 10% to 50% by mass of PMP and 50% to 90% by mass of a plasticizer is melt-kneaded. The mixture preferably contains 15% to 50% by mass of PMP and 50% to 85% by mass of a plasticizer, more preferably contains 20% to 45% by mass of PMP and 55% to 80% by mass of a plasticizer, and particularly preferably contains 25% to 40% by mass of PMP and 60% to 75% by mass of a plasticizer.

[0130] For the device used in the melt kneading of the mixture, a kneader, a roll mill, a Banbury mixer, or a mixer such as a single shaft or a twin shaft extruder can be used. Among them, from the viewpoint of making the uniform dispersibility of the plasticizer good, a twin shaft extruder is preferably used, and from the viewpoint of being able to remove volatiles such as moisture and low molecular weight substances, a twin shaft extruder with a vent hole is more preferably used. In addition, from the viewpoint of improving the mixing strength and making the uniform dispersibility of the plasticizer good, a twin shaft extruder with a screw having a kneading disk portion is preferably used.

[0131] The resin composition obtained in the preparation process can be temporarily granulated, melted again and used for melt film, or can be directly introduced into a die for melt film. When temporarily granulated, it is preferred to use a resin composition in which the particles are dried and the moisture content is below 200ppm (mass basis). By making the moisture content below 200ppm (mass basis), the deterioration of the resin can be suppressed.

[0132] (A2) Forming process

[0133] The resin composition obtained in A1 is discharged from a discharge port die, and after passing through an empty run portion, it is immediately introduced into a cooling bath of a solvent having a solubility parameter distance Ra in the range of 4.0 to 14.0 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb in the range of 3.0 to 6.0 relative to the aforementioned plasticizer, to obtain a molding process of a resin molded product. In the molding process of obtaining a resin product, a hollow fiber membrane is obtained from a molten mixture of a resin composition of PMP and a plasticizer by phase separation. As an example, the resin composition obtained in the preparation process (A1) is discharged from a discharge port die having, for example, a double annular nozzle with a gas flow path arranged in the center into a gas atmosphere, and introduced into a cooling bath to phase separate the resin composition to obtain a resin molded product.

[0134] As a specific method, the above-mentioned resin composition in a molten state is discharged from the outer tube of the double annular nozzle for spinning, and the hollow portion forming gas is discharged from the inner ring of the double tubular die. At this time, it is important that the discharge gap of the discharge die is 0.05mm to 0.30mm. It is speculated that by making the discharge gap of the discharge die in this range, high shear is given to the resin composition in a molten state, thereby easily producing crystallization and promoting the formation of lamellar crystals. After the resin composition discharged in this way moves in the air, it is cooled and solidified in a cooling bath to obtain a resin molding. The discharge gap of the discharge die is more preferably 0.05mm to 0.20mm.

[0135] In addition, the resin composition discharged from the discharge die preferably has at least one of its surfaces, preferably the surface on which the layered crystals are to be formed, exposed to a gaseous atmosphere that promotes the evaporation of the plasticizer, that is, an atmosphere in which the plasticizer can be caused to evaporate, before cooling. The gas used to form the gaseous atmosphere is not particularly limited, and air or nitrogen is preferably used. The gaseous atmosphere usually has a temperature lower than the temperature of the discharge die. In order to form a surface layer in which a layered structure is aggregated and has an open hole, it is important that the distance from the die plane to the solvent plane is 10 mm to 30 mm. It should be noted that in this application, the "distance from the die plane to the solvent plane" is referred to as the "empty distance". The empty distance is preferably 10 mm to 20 mm, more preferably 10 mm to 15 mm.

[0136] Here, a cooling bath for cooling the resin composition discharged from the discharge port die is described. In the manufacture of the separation membrane of the present application, the structure of the membrane surface is affected by the type of solvent in the cooling bath. Therefore, the solvent in the cooling bath is preferably selected based on the affinity of the PMP and the plasticizer.

[0137] When producing a separation membrane by method A, it is important to use a solvent for the cooling bath having a solubility parameter distance Ra of 4.0 to 14.0 with respect to PMP and a solubility parameter distance Rb of 3.0 to 6.0 with respect to the plasticizer.

[0138] The resin composition introduced into the cooling bath is structured by the solvent exchange of the plasticizer and the cooling bath solvent. At this time, if a solvent with a small solubility parameter distance Ra relative to PMP, i.e., a high affinity with PMP, is used, the phase separation of PMP and the plasticizer is difficult to carry out, so the membrane surface of the resulting separation membrane becomes a dense non-porous structure. Alternatively, even in the case of using a solvent with a large solubility parameter distance Rb relative to the plasticizer, i.e., a low affinity with the plasticizer, due to the low exchange efficiency of the solvent and the plasticizer, a dense non-porous structure is also formed on the resulting membrane surface. Therefore, when using a solvent with a large Ra and a small Rb as the solvent of the cooling bath, the phase separation of PMP and the plasticizer is carried out quickly, and the exchange of the solvent and the plasticizer is carried out quickly, thus obtaining a film with surface openings.

[0139] On the other hand, the structure of the film surface is also affected by the cooling rate of the resin composition. When the resin composition is slowly cooled, the layered crystals grow excessively, and the formation of the openings in the cooling bath does not proceed. Therefore, in order to form a film surface with openings on the surface, it is important to make the discharge gap and the air distance within a specified range and quench the resin composition. The inventors found that by quenching the molten resin composition under the conditions of setting the discharge gap to 0.05mm to 0.30mm and the air distance to 10mm to 30mm, and then immediately introducing Ra into a cooling bath of a solvent in the range of 4.0 to 14.0 and Rb in the range of 3.0 to 6.0, it is possible to form a fine opening on the film surface 1 with aggregated layered crystals to a degree that can prevent the solvent from invading the interior of the film.

[0140] When the separation membrane is manufactured by the A method, the spinning stability becomes good when Ra is 4.0 or more. The range of Ra is more preferably 5.0 to 12.0, further preferably 6.0 to 10.0, and particularly preferably 7.0 to 9.0. When the range of Rb is 6.0 or less, a membrane surface with fine openings is formed. The range of Rb is more preferably 3.0 to 5.0, and particularly preferably 3.0 to 4.0. The affinity of PMP to the solvent of the cooling bath can be estimated by the three-dimensional Hansen solubility parameter as described in the literature (Ind. Eng. Chem. Res. 2011, 50, 3798-3817.). Specifically, the smaller the solubility parameter distance (Ra) of the following formula (1), the higher the affinity of the solvent relative to PMP.

[0141] [Number 1]

[0142]

[0143] Here, δ Ad , δ Ap and δ Ah is the dispersion term, polar term and hydrogen bond term of the solubility parameter of PMP, δCd ,δ Cp and δ Ch are the dispersion term, polar term and hydrogen bonding term of the solubility parameter of the solvent.

[0144] The affinity of the plasticizer to the solvent of the cooling bath can also be estimated in the same manner. Specifically, the smaller the solubility parameter distance (Rb) in the following formula (2), the higher the affinity of the plasticizer to the solvent.

[0145] [Number 2]

[0146]

[0147] Here, δ Bd ,δ Bp and δ Bh is the dispersion term, polar term and hydrogen bond term of the solubility parameter of PMP, δ Cd ,δ Cp and δ Ch are the dispersion term, polar term and hydrogen bonding term of the solubility parameter of the solvent.

[0148] When the solvent is a mixed solvent, the solubility parameter (δ Mixture ) can be obtained by the following formula (3).

[0149] [Number 3]

[0150] δ Mixture =Σφ i δ i ……Formula (3)

[0151] Here, δ i is the volume fraction and solubility parameter of component i, which are established in the dispersion term, polar term and hydrogen bond term respectively. Here, "volume fraction of component i" refers to the ratio of the volume of component i before mixing to the sum of the volumes of all components before mixing. The three-dimensional Hansen solubility parameter of the solvent is used when it is recorded in the literature (Ind. Eng. Chem. Res. 2011, 50, 3798-3817.). For unrecorded solvent parameters, the values ​​included in the software "Hansen Solubility Parameter in Practice" developed by Charls Hansen et al. are used. The three-dimensional Hansen solubility parameters of solvents and polymers that are not recorded in the above software can be calculated by using the Hansen sphere method of the above software.

[0152] In the case of producing a separation membrane by the A method, when dibutyl phthalate is used as a plasticizer, the solvent used in the cooling bath of the forming step is preferably Benzoflex (registered trademark) manufactured by Eastman Co., dioctyl phthalate, n-undecyl benzenesulfonate, diisononyl phthalate, butyl benzoate, tocopherol, methylene chloride, butyl benzyl phthalate, diisodecyl phthalate, dimethyl isosorbide, mono(2-ethylhexyl) phthalate, methyl ethyl ketone, methyl propyl ketone, tributyl phosphate, 1, 4-dioxane, ditridecyl phthalate, methyl isoamyl ketone, 1-nitropropane, cyclopentyl methyl ether, N-methylpyrrolidone, sorbitan monooleate, tetrahydrofuran, propylene glycol monostearate, n-butyl propionate, methyl isobutyl ketone, 1,3-dioxolane, n-propyl propionate, acetone, benzyl benzoate, dibasic ester, palmitostearin, methyl oleate, butylene glycol acetate, ascorbyl palmitate, methyl acetate, ethyl acetate; among them, dioctyl phthalate is more preferred because Ra and Rb are within the above-mentioned particularly preferred ranges.

[0153] In the forming process for manufacturing the separation membrane of the present invention, the resin composition discharged from the discharge port die is wound by a winding device. At this time, the value of the draft ratio calculated based on the (winding speed) / (discharge speed from the discharge port die) of the winding device is preferably 1 to 10. The value of the draft ratio is more preferably 1 to 8. By setting the draft ratio to 1 or more, the winding is stable and the change in the fiber shape becomes smaller. By setting the draft ratio to 10 or less, the excessive stretching of the resin composition discharged from the die can be suppressed, and the occurrence of defects on the surface of the hollow fiber membrane can be suppressed.

[0154] (A3) Cleaning process

[0155] The obtained resin molding is immersed in a solvent that does not dissolve the polymer but can be mixed with the plasticizer as needed, thereby extracting the plasticizer and increasing the porosity. The cleaning step is a step of extracting the plasticizer contained in the resin molding into the solvent by introducing the resin molding into a solvent with a solubility parameter distance Ra of 8 to 35 relative to the PMP and a solubility parameter distance Rb of 5 to 35 relative to the plasticizer to obtain a separation membrane. At this time, by using a solvent or a mixed solvent that has a moderate affinity with each of the polymer and the plasticizer, a good solvent exchange can be performed, and the cleaning efficiency is improved.

[0156] By making the solubility parameter distance Ra of the cleaning solvent relative to PMP 8 or more, the shape stability of the resin composition becomes good, and by making it 35 or less, the resin composition swells appropriately and the cleaning efficiency is improved. The range of Ra is preferably 10 to 25, and particularly preferably 12 to 22. By making the solubility parameter distance Rb of the cleaning solvent relative to the plasticizer 35 or less, good solvent exchange can be performed and the cleaning efficiency is improved. The range of Rb is preferably 10 to 25, and particularly preferably 12 to 22.

[0157] As the solvent used in the cleaning step, when dibutyl phthalate is used as the plasticizer, methyl isobutyl ketone, acetone, butylene acetate, methyl acetate, propylene glycol monoethyl ether acetate, Benzoflex (registered trademark) manufactured by Eastman Co., Ltd., N,N-dimethylacetamide, dipropylene glycol monobutyl ether, diethylene glycol monobutyl ether, t-butyl acetate, propylene glycol monomethyl ether acetate, diacetone alcohol, ε-caprolactone, isopropyl acetate, sec-butyl acetate, propylene glycol monobutyl ether, TEXANOL, γ-butyrolactone, tetrahydrofurfuryl alcohol, N,N-dimethylformamide, dipropylene glycol methyl ether, propylene glycol monomethyl ether acetate, Methyl ether, triethyl citrate, methyl carbitol, ethyl lactate, ethylene glycol monobutyl ether, dimethylcyclohexane, benzyl alcohol, dimethyl sulfoxide, propylene carbonate, cyclohexanol, glycerol diacetate, isopentanol, 2-phenoxyethanol, heptane, acetonitrile, n-pentanol, methyl isobutyl carbinol, tetramethylene sulfone, hexane, VM&P naphtha, hexylene glycol, ethylene glycol monomethyl ether, 2-butanol, tert-butanol, 1-butanol, ethylene carbonate, isopropanol, isobutanol, 1-propanol, dipropylene glycol, ethanol, propylene glycol, methanol, glycerol carbonate, ethylene glycol; among them, methanol, ethanol, and isopropanol are more preferred because Ra and Rb are within the above-mentioned particularly preferred ranges.

[0158] The resin product in the cleaning process is stretched in the process as needed to crack between the layered structures, thereby further controlling the pore size and porosity of the membrane surface. In order to improve the gas permeability by effective opening, the stretching ratio is preferably set to 1.1 times or more. On the other hand, when the area occupied by the opening portion increases, it is difficult to suppress the solvent from invading the interior of the membrane, so the solvent resistance is easily reduced. Therefore, the stretching ratio is preferably set to 5.0 times or less. The stretching ratio is more preferably 1.2 to 3.0, and particularly preferably 1.5 to 2.0.

[0159] The temperature of the washing solvent is preferably 10 to 50° C. When the temperature is 10° C. or higher, the flexibility of the resin molded product becomes good, and when the temperature is 50° C. or lower, the structure of the film surface can be maintained. The temperature of the washing solvent is more preferably 20 to 45° C., and particularly preferably 25 to 40° C.

[0160] Next, each step of method B for obtaining the separation membrane of the present invention will be described.

[0161] (B1) Preparation process

[0162] The preparation step (B1) of obtaining the resin composition is carried out in the same manner as the preparation step (A1) of the A method.

[0163] (B2) Forming process

[0164] The resin composition obtained in B1 is discharged from the discharge port die, passed through the idling section, and immediately introduced into a cooling bath of a solvent having a solubility parameter distance Ra of 5.0 to 18.0 with respect to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 1.0 to 2.9 or 6.5 to 10.0 with respect to the aforementioned plasticizer, to obtain a molding of a resin. The molding step (B2) of obtaining a molding of a resin can be carried out by the same steps as the molding step (A2) of the A method, but differs in the following aspects.

[0165] When the separation membrane is manufactured by the B method, the membrane surface of the resin molded product obtained in the (B2) molding step is preferably a non-porous structure with layered crystals. Therefore, as a solvent for the cooling bath, it is important to use a solvent in the cooling bath whose solubility parameter distance Ra relative to PMP is in the range of 5 to 18 and whose solubility parameter distance Rb relative to the plasticizer is in the range of 1.0 to 2.9 or 6.5 to 10.0. A preferred membrane surface is formed by Ra and Rb being in the aforementioned range. It is speculated that by Ra being in the range of 5 to 18, solidification occurs before the crystallization of PMP, and by Rb being in the range of 1.0 to 2.9 or 6.5 to 10.0, the exchange of the solvent and the plasticizer is carried out at an appropriate speed, thereby forming a non-porous structure. It is more preferred to use a solvent in the cooling bath whose Ra is in the range of 5.0 to 7.0 and whose Rb is in the range of 6.5 to 10.0.

[0166] In the case of producing a separation membrane by the B method, as the solvent used in the cooling bath of the (B2) forming step, when dibutyl phthalate is used as a plasticizer, preferably cyclohexanone, diethyl phthalate, isophorone, dihexyl phthalate, Benzoflex (registered trademark) manufactured by Eastman Co., Ltd., diisoheptyl phthalate, dimethyl phthalate, fatty acid methyl ester, n-butyl acetate, n-amyl acetate, triacetin, N,N-dimethylacetamide, butyl diethylene glycol acetate, acetyl triethyl citrate, n-propyl acetate, dipropylene glycol mono-n-butyl ether, diethylene glycol monobutyl ether, t-butyl acetate, ethyl 3-ethoxypropionate, propylene glycol monomethyl ether acetate, diacetone alcohol, isoamyl acetate, tri-n-butyl citrate, Exxon Solvesso (registered trademark) 100 manufactured by Mobil Corporation, isobutyl isobutyrate, ε-caprolactone, propylene glycol phenyl ether, isopropyl acetate, sec-butyl acetate, propylene glycol monobutyl ether, TEXANOL, Solvesso 150, ethylbenzene, γ-butyrolactone, tetrahydrofurfuryl alcohol, N,N-dimethylformamide, dipropylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol monomethyl ether, triethyl citrate, methyl carbitol, ethyl lactate, ethylene glycol monobutyl ether, cyclohexane, methylcyclohexane, dimethylcyclohexane, benzyl alcohol, and dimethyl sulfoxide. Among them, triacetin is more preferred because Ra and Rb are within the above-mentioned more preferred ranges.

[0167] In addition, unlike the forming step (A2), the idling distance is not particularly limited, and the idling distance of the forming step (B2) is preferably 10 to 80 mm. The idling portion of 10 to 80 mm makes the thickness of the surface layer good. The idling distance is preferably 10 to 60 mm, more preferably 10 to 40 mm, and particularly preferably 10 to 30 mm.

[0168] (B3) Cleaning process

[0169] The process of washing the separation membrane is carried out by introducing the resin molded product obtained in B2 into a solvent having a solubility parameter distance Ra of 8 to 35 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 5 to 35 relative to the aforementioned plasticizer, and stretching it to 1.1 to 5.0 times, and at the same time extracting the aforementioned plasticizer contained in the aforementioned resin molded product into the solvent. (B3) The need for stretching in the washing process is different from the A method. (B3) The washing process can be carried out using the same solvent as the washing process (A3) of the A method, but it is important to stretch during the process. Thereby, cracks are created between the layered structures on the surface of the non-porous membrane, and a membrane surface having both layered crystals and micropores can be formed.

[0170] Generally, it is known that the layered crystals are cleaved by stretching to form a porous structure on the surface and inside of the separation membrane. However, this method only cleaves specific pores, i.e., weakly bonded parts, which may lead to the formation of coarse pores and breakage during transportation.

[0171] Therefore, if the polymer is plasticized and swollen by using a plasticizer and a cleaning solvent, it is expected that the same structure formation can be performed without defects, and a film with micropores formed between the layered crystals can be obtained. The inventors have found that by stretching in the cleaning process, an open hole portion of a degree that can prevent the solvent from invading the inside of the film can be formed on the surface 1 of the film with aggregated layered crystals with a high open porosity.

[0172] In order to improve the gas permeability by effective opening, the stretching ratio is preferably set to 1.1 times or more. On the other hand, when the area occupied by the opening increases, it is difficult to suppress the intrusion of the solvent into the film, so the solvent resistance is easily reduced. Therefore, the stretching ratio is preferably set to 5.0 times or less. The stretching ratio is more preferably 1.2 to 3.0, and particularly preferably 1.5 to 2.0.

[0173] Moreover, for the same reason as in the washing step (A3), the temperature of the washing solvent is preferably 10 to 50°C, more preferably 20 to 45°C, and particularly preferably 25 to 40°C.

[0174] In the manufacture of the separation membrane of the present invention, a drying step may be performed after the washing step (A3) or (B3). In order to remove the attached solvent by the washing step, the resin molded product is preferably subjected to a drying step. The drying is preferably performed at a temperature at which the washing solvent can be vaporized and removed, and specifically, it is preferably performed at room temperature to 150° C. In this way, the separation membrane of the present invention having PMP as a main component can be manufactured.

[0175] (Degassing components)

[0176] The degassing assembly is a constituent unit for separating gas from liquid. The separation membrane of the present invention obtained as described above can be filled into a housing by a known method to form a degassing assembly. For example, a hollow fiber membrane assembly has a plurality of hollow fiber membranes and a cylindrical housing. After a plurality of hollow fiber membranes are bundled and inserted into a cylindrical housing, the ends are fixed to the above-mentioned housing with a thermosetting resin such as polyurethane or epoxy resin and sealed. The ends of the hollow fiber membranes cured with the thermosetting resin are cut off to obtain the opening surface of the hollow fiber membrane, thereby making a degassing assembly.

[0177] It should be noted that in the degassing assembly having the separation membrane of the present application, the liquid to be treated is water, an organic solvent and a mixture thereof. The liquid may not contain a hydrocarbon solvent. The liquid may be selected from at least one of glycols, glycol monoalkyl ethers, glycol dialkyl ethers, glycol monoacetates, glycol diacetates, alcohols, ketones, acetates, lactates, saturated hydrocarbons, unsaturated hydrocarbons, cyclic saturated hydrocarbons, cyclic unsaturated hydrocarbons, aromatic hydrocarbons, terpenes, ethers, cyclic imides, 3-alkyl-2-oxazolidinones, N-alkylpyrrolidones, lactones and nitrogen-containing solvents. The liquid may also be UV ink or ceramic ink.

[0178] Example

[0179] The present invention is further described in detail with reference to the following examples, but the present invention is not limited to these examples. [Measurement and Evaluation Methods] The characteristic values ​​in the examples were determined by the following methods.

[0180] (1) Outer and inner diameters of hollow fiber membranes (μm)

[0181] After freezing the hollow fiber membrane with liquid nitrogen, stress is applied (using a razor or microtome as needed), and the exposed cross section is observed with an optical microscope. The average values ​​of the outer diameter and inner diameter of 10 randomly selected points are set as the outer diameter and inner diameter of the hollow fiber membrane, respectively.

[0182] (2) Hollowness ratio of hollow fiber membrane (%)

[0183] The hollowness of the hollow fiber membrane was calculated by the following formula from the outer diameter and inner diameter obtained in the above (1).

[0184] Hollowness (%) = [Inner diameter (μm 2 )] 2 / [Outer diameter (μm 2 )] 2 ×100.

[0185] (3) A small module with an effective length of 100 mm including three gas permeability performance (GPU) hollow fiber membranes was prepared. Specifically, three hollow fiber membranes were bundled and inserted into a plastic tube as a cylindrical shell, and then the gaps between the membranes and the gaps with the tube were cured and sealed with a thermosetting resin at the ends of the hollow fiber membrane bundle. The open surface of the hollow fiber membrane was obtained by cutting the ends of the sealed hollow fiber membranes, thereby preparing a small module for evaluation. Using this small module, the gas permeation flow rate was measured. As the measuring gas, carbon dioxide or nitrogen was used alone for evaluation, and the pressure change of the permeation side of carbon dioxide or nitrogen per unit time was measured by an external pressure method at a measuring temperature of 37°C. Here, the pressure difference between the supply side and the permeation side was set to 100 kPa. The temperature of the gas was set to 37°C. The differential pressure of 100 kPa means that the pressure difference between the gas supply side and the permeation side of the separation membrane is 100 kPa.

[0186] Next, the gas permeation flow rate Q is calculated by the following formula (4), and the value is defined as the gas permeability performance. Here, J is the gas flow, P is the gas permeation rate, and H and P L GPU is a common unit for expressing the gas permeation flow rate Q. 1GPU = 3.35 × 10 -10 mol / m 2 ·s·Pa. In addition, the ratio of the gas permeation flow rate Q of each component is defined as the separation coefficient α.

[0187] [Number 4]

[0188]

[0189] (4) Surface thickness (μm)

[0190] After freezing the separation membrane with liquid nitrogen in the same manner as in the above (1), stress is applied (using a razor, a microtome, or a wide ion beam as needed) to cut the separation membrane so that a radial section or a longitudinal section is exposed. Next, the radial section or the longitudinal section is pre-treated by sputtering with platinum, and then observed using a SEM at a magnification of 10,000 times. When a straight line perpendicular to the outer surface is drawn from an arbitrary point on the outer surface of the separation membrane to the inner surface side (inner layer side), the length until the first hole exceeding 50 nm is reached is defined as the surface thickness.

[0191] The extraction of the inner layer pores that determine the thickness of the surface layer was performed by binarizing the analyzed image using the image analysis software "ImageJ". Figure 3 to Figure 5 Provide explanation. Figure 3 This is an example of an image observed at a magnification of 10,000 times using a SEM. Figure 4 Yes Figure 3The processed image of the surface cross section obtained by removing the noise after binarization. The binarization is performed as follows, that is, when the horizontal axis represents the brightness in the analysis image and the vertical axis represents the number of pixels at the corresponding brightness, the number of pixels at the brightness with the highest number of pixels is set to A, and the smaller brightness of the two points corresponding to the number of pixels becoming 1 / 2A is implemented. Furthermore, for the obtained binarized image, noise removal is performed once to replace all pixels with the central value of 3×3 pixels near the pixel (equivalent to Despeckle in ImageJ), and the obtained image is used as the analysis image. Figure 5 As described above, a line perpendicular to the outer surface is drawn from an arbitrary point on the outer surface of the obtained image toward the inner surface, and the length until the hole exceeding 50 nm is first reached is calculated. It should be noted that the measurement is performed at 10 arbitrary points, and the average value is used as the surface layer thickness.

[0192] (Sputtering)

[0193] Device: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0194] Evaporation time: 40 seconds Current value: 20mA

[0195] (SEM)

[0196] Device: Made by Hitachi High-Technology Co., Ltd. (SU1510)

[0197] Accelerating voltage: 5 kV. Probe current: 30 pA.

[0198] (5) Area ratio of lamellar crystals on the film surface (%)

[0199] After the surface with the layered crystal side was pre-treated by sputtering with platinum, when observed with SEM at a magnification of 60,000 times, the area of ​​the layered crystal, that is, the bright part of the SEM image, was extracted, and the area ratio occupied in the entire observed image was calculated. The extraction of layered crystals is performed after binarizing the analyzed image (Otsu's binarization) in the image analysis software "ImageJ". For the obtained binary image, noise removal (equivalent to Despeckle in ImageJ) was performed 5 times to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image was used as the analyzed image. Using the Analyze Particles command of ImageJ, all the obtained bright parts were extracted, and the area ratio occupied by the layered crystals was calculated from the area of ​​the obtained bright parts. It should be noted that the measurement is performed on any 5 places, and the average value is used as the area ratio occupied by the layered crystals in the entire observed image. It should be noted that by calculating the proportion of layered crystals in the observed image, it can be used as the proportion of layered crystals on the surface of the film.

[0200] (Sputtering) Equipment: Made by Hitachi High-Technology Co., Ltd. (E-1010)

[0201] Evaporation time: 40 seconds Current value: 20mA

[0202] (SEM) Equipment: Made by Hitachi High-Technology Co., Ltd. (S5500)

[0203] Accelerating voltage: 5 kV. Probe current: 30 pA.

[0204] (6) Average pore size of the micropores on the membrane surface (nm)

[0205] The surface with the layered crystals was pretreated by sputtering with platinum under the same conditions as in (5). Holes with a diameter of more than 1 nm, i.e., an area of ​​more than 0.785 nm, were observed using a SEM at a magnification of 60,000 times. 2 All the holes are extracted, and the pore size when the holes are regarded as perfect circles is calculated from the area, and the average value is set as the surface pore size. The extraction of the holes is performed after the analysis image is binarized (Huang's binarization) in the image analysis software "ImageJ". Furthermore, for the obtained binarized image, noise removal (equivalent to Despeckle in ImageJ) is performed once to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image is used as the analysis image. The extraction of the holes is performed by the Analyze Particles command of ImageJ, and the surface pore size is calculated based on the area of ​​the obtained holes. It should be noted that the measurement is performed on any 5 places, and the average value is set as the average pore size of the micropores on the membrane surface.

[0206] (7) Opening rate of micropores on the membrane surface (%)

[0207] The surface with the layered crystals was pretreated by sputtering with platinum under the same conditions as in (5). Holes with a diameter of more than 1 nm, i.e., an area of ​​more than 0.785 nm, were observed using a SEM at a magnification of 60,000 times. 2All the holes are extracted, and the area ratio of the open parts when the area of ​​the entire observed image is set to 100% is calculated from the number and area of ​​the holes, which is set as the porosity of the membrane surface. The extraction of holes is performed after the analysis image is binarized (Huang's binarization) in the image analysis software "ImageJ". Furthermore, for the obtained binarized image, noise removal (equivalent to Despeckle in ImageJ) is performed once to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image is used as the analysis image. The extraction of holes is performed by the Analyze Particles command of ImageJ, and the area ratio of the open parts in the entire observed image is calculated based on the number and area of ​​the holes obtained. It should be noted that the measurement is performed on any 5 places, and the average value is set as the porosity of the membrane surface.

[0208] (8) Every 1 μm 2 The number of openings on the membrane surface (number / μm 2 )

[0209] The surface with the layered crystals was pretreated by sputtering with platinum under the same conditions as in (5). Holes with a diameter of more than 1 nm, i.e., an area of ​​more than 0.785 nm, were observed using a SEM at a magnification of 60,000 times. 2 All the holes in the observation area were extracted and the number of holes was set as the number of holes in the observation area. The hole extraction was performed using the image analysis software "ImageJ" under the same conditions as (7). Next, the area of ​​the observation area was calculated and the number of holes per unit area (1 μm) was calculated using the following formula: 2 ) The number of openings. It should be noted that the measurement was performed at 5 random locations, and the average value was set as the number of openings per 1 μm. 2 The number of openings on the membrane surface.

[0210] Every 1μm 2 The number of openings on the membrane surface (number / μm 2 ) = Number of openings in the observation area (pieces) / Area of ​​the observation area (μm 2 )

[0211] (9) Area ratio of lamellar crystals in the film surface excluding the openings (%)

[0212] Based on the area ratio of the layered crystals in the entire observed image obtained by (5) above and the porosity obtained by (6) above, the area ratio of the layered crystals in the surface excluding the openings is calculated by the following formula and is set as the area ratio of the layered crystals in the film surface.

[0213] Area ratio of lamellar crystals (%) = Area ratio of lamellar crystals in the entire observed image (%) / (1-opening ratio (%))

[0214] In the above (5), when no open pores are observed on the surface, the area ratio of the layered crystals in the entire observed image obtained by (5) is defined as the area ratio of the layered crystals in the film surface.

[0215] (10) Porosity of membrane cross section (%)

[0216] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, stress is applied (using a razor, microtome, or wide ion beam as needed) to cut the membrane so that the radial section or longitudinal section is exposed. Next, under the same conditions as in (4) above, the radial section or longitudinal section is pre-treated by sputtering with platinum, and then observed using SEM at a magnification of 10,000 times, the area of ​​the pore portion, that is, the dark portion of the SEM image, is extracted, and the area ratio occupied in the entire observed image is calculated and set as the opening rate of the membrane cross section. The extraction of the pore portion is performed after binarizing the analyzed image (Huang's binarization) in the image analysis software "ImageJ". For the obtained binarized image, noise removal (equivalent to Despeckle in ImageJ) is performed once to replace all pixels with the central value of 3×3 pixels near the pixel, and the obtained image is used as the analyzed image. The extraction of the pores is performed using the Analyze Particles command of ImageJ, all the obtained dark portions are extracted, and the area ratio occupied by the pore portion is calculated from the area of ​​the obtained dark portion. The measurement was performed at 5 arbitrary locations, and the average value thereof was used as the average porosity in the membrane cross section.

[0217] (11) Number of pores larger than 10 μm in the membrane cross section

[0218] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, stress is applied (using a razor, a microtome, or a wide ion beam as needed) to cut the membrane so that the radial section or the longitudinal section is exposed. Then, under the same conditions as in (4) above, the membrane is pre-treated by sputtering with platinum. When observed using an SEM at a magnification of 2,000 times, the pores with a diameter greater than 10 μm per field of view, i.e., the pores with an area greater than 78.5 μm, are removed. 2All the holes are extracted and their number is calculated. It should be noted that the diameters of the holes at the ends of the image that are not in the field of view as a whole are also calculated in this state. The extraction of the holes is performed after the analysis image is binarized (Huang's binarization) in the image analysis software "ImageJ". Furthermore, for the obtained binarized image, noise removal is performed once to replace all pixels with the central value of 3×3 pixels near the pixel (equivalent to Despeckle in ImageJ), and the obtained image is used as the analysis image. The extraction of the holes is performed using the Analyze Particles command of ImageJ, and the number of the obtained holes is calculated. It should be noted that the measurement is performed on any 5 locations, and the average value is used as the number of empty holes larger than 10μm in the membrane cross section.

[0219] (12) The ratio of the major axis length a to the minor axis length b of the inner layer pores is a / b

[0220] After freezing the separation membrane with liquid nitrogen in the same manner as in (1) above, the membrane is cut using a microtome to expose a longitudinal section. The obtained slice is pre-treated by sputtering with platinum under the same conditions as in (5), and then observed using an SEM at a magnification of 10,000 times. A hole is randomly selected from the obtained observation image, and the major axis length a and minor axis length b of the hole are determined. It should be noted that holes that cannot be regarded as approximately ellipses are removed from the measurement objects. In the measurement, holes in which more than 50% of the length a of the major axis exists in the hole when the major axis is connected at both ends by a straight line are used. In the following, the following is used. Figure 6 (a) to (c) are explained. Figure 6 In (a) to (c), the major axis length a of the pore refers to the length of the longest straight line 9 in the straight line that can directly connect two points on the outer edge of the pore. Here, the line segment 9 does not necessarily have to be parallel to the longitudinal direction of the hollow fiber (see Figure 6 (b), (c)). In addition, the minor axis length b refers to the length of the longest straight line 10 in the straight line that can directly connect two points on the outer edge of the hole. Here, the straight lines 9 and 10 do not necessarily have to intersect ( Figure 6 (c) Reference). Based on the major axis length a and the minor axis length b obtained above, the ratio a / b of the major axis length a to the minor axis length b was calculated by the following formula. It should be noted that the measurement was performed at 5 locations, and the average value was used as the ratio a / b of the major axis length a to the minor axis length b of the pores in the inner layer.

[0221] a / b=long axis length of pore a (nm) / short axis length of pore b (nm).

[0222] (13) Porosity of separation membrane (%)

[0223] When the separation membrane is in the form of a hollow fiber membrane, the fiber length L (mm) and mass M (g) of the hollow fiber membrane dried in vacuum at 25° C. for 8 hours are measured. Density ρ of the hollow fiber membrane 1 It is calculated by the following formula using the values ​​of the outer diameter (mm) and the inner diameter (mm) measured in the above (1).

[0224] ρ 1 =M / [π×{(outer diameter / 2) 2 -(inner diameter / 2) 2}×L]

[0225] In addition, the porosity ε (%) was calculated by the following formula.

[0226] ε=1-ρ 1 / ρ 2

[0227] Here, ρ 2 is the density of the polymer.

[0228] (14) Period length of layered crystals on the film surface (nm)

[0229] The surface having the layered crystals was pretreated by sputtering with platinum under the same conditions as in (5), and then the period length of the layered crystals was calculated when observed using a SEM at a magnification of 30,000. The calculation was performed using the image processing software ImageJ according to the following method.

[0230] A. SEM images were read in using Image-J (file size was set to 512 × 512 pixels).

[0231] B. When executing Process / FFT / FD Math, the autocorrelation function is output as an image as the Result, so the image type is set to 16 bit.

[0232] C. Use the line tool to draw a horizontal line through the bright point in the center of the image.

[0233] D. Execute Analyze / Plot Profile and output Plot of Result.

[0234] E. Press the List button to output the intensity and distance and create a graph.

[0235] F. Measure the distance from the brightness of the center of the autocorrelation function (output image) to the first proximal peak and calculate the cycle length.

[0236] (15) Crystallinity of film surface (%)

[0237] The surface of the hollow fiber membrane that had been vacuum dried at 25°C for 8 hours was measured by ATR spectrum using an FTIR (FTS-55A) manufactured by BioRad DIGILAB equipped with a single reflection ATR accessory. It should be noted that for ATR crystallization, a diamond prism was used with an incident angle of 45° and 64 accumulations. Based on the obtained ATR spectrum, the crystallinity was calculated using the intensity ratio of the specified bands. In the case of the hollow fiber membrane of PMP, 849 cm -1 The intensity of the band near 1169 cm -1 The intensity of the band nearby is calculated by the following formula.

[0238] IR intensity ratio of the outer surface = [849cm -1 Band intensity near] / [1169cm -1 Band intensity near

[0239] Crystallinity (%) = 172.9 × IR intensity ratio of the outer surface.

[0240] [PMP raw materials]

[0241] The PMP raw material used was TPX (registered trademark) DX845 (density: 833 kg / m 3 , MFR: 9.0g / 10min).

[0242] (Example 1)

[0243] PMP35 mass% and 65 mass% of dibutyl phthalate as a plasticizer are supplied to a twin-shaft extruder, melt-kneaded at 290°C, and then introduced into a melt spinning kit with a spinning temperature set to 245°C, and spun downward from the outer annular portion of the discharge die with one die hole (double circular tube type, discharge aperture 1.2mm, discharge gap 0.20mm). The spun hollow fiber is introduced into a cooling bath of dioctyl phthalate and wound with a winding machine in a draft ratio of 3.5. At this time, the empty distance is set to 10mm. Here, a metal filter with a diameter of 100μm is used as a filter in the melt spinning kit. The wound hollow fiber is immersed in isopropanol for 24 hours, and then vacuum dried at room temperature to remove isopropanol to obtain a hollow fiber membrane. The stretching in the cleaning process is not performed, that is, the stretching ratio is set to 1.0. The physical properties of the obtained hollow fiber membrane are shown in Table 1. In the membrane surface with layered crystals on the obtained hollow fiber membrane, the average pore size of the micropores was 16 nm, the porosity was 1.4%, the area ratio of the layered crystals was 35%, and the period of the layered crystals was 39 nm. 2 The permeability is 7733GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2The permeability is 494GPU, which has excellent permeability and high resistance to organic solvents.

[0244] (Example 2)

[0245] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was butyl benzoate to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 18 nm, the open porosity was 0.8%, the area ratio of layered crystals was 34%, and the period of layered crystals was 46 nm. 2 The permeability is 11049GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The performance through is 217GPU.

[0246] (Example 3)

[0247] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was N-methylpyrrolidone to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 25 nm, the open porosity was 0.2%, the area ratio of layered crystals was 47%, and the period of layered crystals was 26 nm. 2 The permeability is 14979GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The throughput is 6 GPU.

[0248] (Example 4)

[0249] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was changed to benzyl benzoate to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 20 nm, the open porosity was 0.1%, the area ratio of layered crystals was 37%, and the period of layered crystals was 35 nm. 2 The permeability is 12623GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The throughput is 10 GPU.

[0250] (Example 5)

[0251] PMP35 mass% and 65 mass% of dibutyl phthalate as a plasticizer are supplied to a twin-shaft extruder, melt-kneaded at 290°C, and then introduced into a melt spinning kit with a spinning temperature set to 245°C, and spun downward from the outer annular portion of the discharge die with one die hole (double circular tube type, discharge aperture 1.2mm, discharge gap 0.20mm). The spun hollow fiber is introduced into a cooling bath of N-methylpyrrolidone and wound with a winding machine in a draft ratio of 3.5. At this time, the empty distance is set to 10mm. Here, a metal filter with a diameter of 100μm is used as a filter in the melt spinning kit. Then, as a cleaning process, the obtained hollow fiber is stretched to 1.2 times in isopropanol at 40°C at a stretching speed of 2% / second, immersed for 24 hours, and then vacuum dried at room temperature to remove isopropanol to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size is 29 nm, the porosity is 0.5%, the area ratio of layered crystals is 45%, and the period of layered crystals is 30 nm. 2 The permeability is 23623GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The throughput is 24 GPU.

[0252] (Example 6)

[0253] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was set to triacetin and the stretching ratio in the washing step was set to 1.8 times to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 10 nm, the open porosity was 1.9%, the area ratio occupied by layered crystals was 46%, and the period of layered crystals was 43 nm. In addition, N 2 The permeability is 23267GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The performance through is 1163GPU.

[0254] (Example 7)

[0255] The same procedure as in Example 1 was followed except that the stretching ratio in the washing step was set to 1.2 times to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 19 nm, the open porosity was 2.0%, the area ratio occupied by layered crystals was 33%, and the period of layered crystals was 47 nm. 2 The permeability is 18740GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The throughput is 94GPU.

[0256] (Example 8)

[0257] The same procedure as in Example 1 was followed except that the stretching ratio in the washing step was set to 1.8 times to obtain a hollow fiber membrane. The results are shown in Table 1. On the membrane surface with layered crystals, the average pore size was 24 nm, the open porosity was 4.9%, the area ratio occupied by layered crystals was 29%, and the period of layered crystals was 55 nm. 2 The permeability is 25333GPU, chloroform / isopropanol = 1 / 1 (volume / volume) after immersion 2 The throughput is 8GPU.

[0258] (Comparative Example 1)

[0259] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was changed to triacetin to obtain a hollow fiber membrane. The stretching in the washing step was not performed, that is, the stretching ratio was set to 1.0. The results are shown in Table 1. No openings were observed on the membrane surface having the layered crystals. 2 The permeability is a low value of 40 GPU. The area ratio of the layered crystals in the membrane surface is 54%, the period of the layered crystals is 23 nm, and the N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) 2 The performance through is 39GPU.

[0260] (Comparative Example 2)

[0261] The same procedure as in Example 1 was followed except that the solvent of the cooling bath was dimethyl phthalate to obtain a hollow fiber membrane. The stretching in the washing step was not performed, that is, the stretching ratio was set to 1.0. The results are shown in Table 2. No openings were observed on the membrane surface having layered crystals. 2 The permeability is a low value of 158 GPU. The area ratio of the layered crystals in the membrane surface is 58%, the period of the layered crystals is 18 nm, and the N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) 2 The throughput is 15 GPU.

[0262] (Comparative Example 3)

[0263] The hollow fiber membrane was obtained in the same manner as in Example 3 except that the air-passing distance was set to 35 mm. The stretching in the washing step was not performed, that is, the stretching ratio was set to 1.0. The results are shown in Table 2. No openings were observed on the membrane surface having the layered crystals. 2 The permeability is a low value of 150 GPU. The area ratio of the layered crystals in the membrane surface is 55%, the period of the layered crystals is 40 nm, and the N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) 2 The throughput is 17 GPU.

[0264] (Comparative Example 4)

[0265] The same procedure as in Example 1 was followed except that the discharge gap was set to 0.35 mm, the draft ratio was set to 231, the air distance was set to 20 mm, and the solvent of the cooling bath was set to triacetin, to obtain a hollow fiber membrane. The stretching in the washing step was not performed, that is, the stretching ratio was set to 1.0. The results are shown in Table 2. No lamellar crystals were observed on the membrane surface having a dense surface layer (that is, the area ratio of lamellar crystals was 0%), and N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) was 0.1%. 2 The performance is 0 GPU, which is displayed as a low value. 2 The transmittance performance is lower than that of GPU5, which is poor.

[0266] (Comparative Example 5)

[0267] The spinning was performed with PMP set to 100 mass % and the draft ratio set to 700, and air cooling was performed without using a cooling bath. After air cooling, the stretching temperature was set to 130°C, and the stretching ratio was set to 2.3 times. The same procedure as in Example 1 was followed to obtain a hollow fiber membrane. It should be noted that since there was no cooling bath, there was no air distance. No plasticizer was used in the raw material, but the wound hollow fiber was immersed in isopropanol for 24 hours, and then vacuum dried at room temperature to remove the isopropanol to obtain a hollow fiber membrane. The hollow fiber membrane was stretched, but the stretching in the cleaning process was not performed. In Table 2, stretching is excluded. The results are shown in Table 2. The porosity is 20%, N 2 The permeability is a low value of 3GPU. The area ratio of the layered crystals on the membrane surface is very low at 1%, and the period cannot be calculated. Chloroform / isopropanol = 1 / 1 (volume / volume) N after immersion 2 The performance is shown as a low value for 2GPU.

[0268] (Comparative Example 6)

[0269] The spinning was performed with PMP set to 100% by mass and the draft ratio set to 750, and air cooling was performed without using a cooling bath. After air cooling, the unstretched spun fiber was heat treated at 190°C for 2 hours while being wound on a bobbin, and then the stretching temperature was set to 130°C, and the stretching ratio was set to 2.3 times for stretching. Otherwise, the same procedure as in Example 1 was followed to obtain a hollow fiber membrane. It should be noted that since there was no cooling bath, there was no empty distance. No plasticizer was used in the raw material, but the wound hollow fiber was immersed in isopropanol for 24 hours, and then vacuum dried at room temperature to remove the isopropanol to obtain a hollow fiber membrane. The hollow fiber membrane was stretched, but the stretching in the cleaning process was not performed. In Table 2, stretching is set as an exception. The results are shown in Table 2. No dense surface layer was observed, and the membrane as a whole was a microporous structure. The area ratio of the layered crystals on the membrane surface was as low as 9%, and the period could not be calculated. Chloroform / isopropanol = 1 / 1 (volume / volume) N after immersion 2 The performance is 0 GPU, which is displayed as a low value.

[0270] (Comparative Example 7)

[0271] The spinning was performed with PMP set to 100% by mass, the discharge gap set to 1.0 mm, the draft ratio set to 400, and air cooling was performed without using a cooling bath. After air cooling, the spun fiber was stretched with a stretch ratio of 2.0 times, and then relaxed to 0.8 times at 190°C, and heat fixed for about 1 second. Otherwise, the same procedure as in Example 1 was followed to obtain a hollow fiber membrane. It should be noted that since there was no cooling bath, there was no air distance. No plasticizer was used in the raw material, but the wound hollow fiber was immersed in isopropanol for 24 hours, and then vacuum dried at room temperature to remove the isopropanol to obtain a hollow fiber membrane. The hollow fiber membrane was stretched, but the stretching in the cleaning process was not performed. In Table 2, stretching is set as excluded. The results are shown in Table 2. No layered crystals were observed on the membrane surface with a dense surface layer (i.e., the area ratio of layered crystals was 0%), and N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) 2 The performance is 0 GPU, which is displayed as a low value.

[0272] (Comparative Example 8)

[0273] The same procedure as in Example 6 was performed except that the stretching ratio in the washing step was set to 1.05 times to obtain a hollow fiber membrane. The results are shown in Table 2. 2 The performance is 646GPU, which is shown as a low value.

[0274] [Table 1]

[0275]

[0276] [Table 2]

[0277]

[0278] In the separation membranes obtained in Examples 1 to 8, the average pore size, open porosity, area ratio occupied by the lamellar crystals, and period of the lamellar crystals on the membrane surface having the lamellar crystals satisfy the requirements of the present invention, N 2 The permeability is above 1000 GPU, and the N after immersion in chloroform / isopropanol = 1 / 1 (volume / volume) 2 The permeability is 5 or more, and the permeability is excellent and has high resistance to organic solvents. On the other hand, the separation membranes of Comparative Examples 1 to 3 that do not have openings on the membrane surface and the separation membrane of Comparative Example 8 whose membrane surface opening ratio does not meet the requirements of the present invention show N 2 The permeability was low. Furthermore, the separation membranes of Comparative Examples 4 to 7 that did not have aggregated lamellar crystals on the membrane surface were immersed in chloroform / isopropanol = 1 / 1 (volume / volume). 2 The permeability showed a low value. In any of Examples 1 to 8, the number of pores larger than 10 μm in the inner layer was zero.

[0279] Industrial Applicability

[0280] The separation membrane of the present invention can be suitably used for separating gas from liquid or imparting gas to liquid. For example, in semiconductor production lines, liquid crystal color filter production lines, and inkjet printer ink manufacturing, it can be suitably used as a degassing membrane for reducing the amount of dissolved gas in water, aqueous solutions, organic solvents, and resist liquids, or as a gas exchange membrane in an artificial lung for medical purposes. In particular, as a degassing membrane, it is very useful in the degassing purposes of photoresist liquid and developer used in the photolithography of semiconductor production lines.

[0281] Explanation of symbols

[0282] 1 Membrane surface

[0283] 2 Opening

[0284] 3 Surface

[0285] 4 Inner layer

[0286] 5 Surface thickness

[0287] 6 Layered crystals

[0288] 7. Void (hole)

[0289] 8 Hollow fiber shaped separation membrane

[0290] a Long axis of the hole

[0291] b Minor axis of the hole

Claims

1. A separation membrane comprising poly(4-methyl-1-pentene) as a main component and comprising a surface layer and an inner layer, wherein: Having lamellar crystals in at least one surface layer, The surface layer having the layered crystals has micropores. When the ratio of the micropores to the membrane surface is defined as the opening rate and the membrane surface is defined as 100%, the opening rate is 0.1% to 10%, and the average pore size of the micropores is 3nm to 30nm.

2. The separation membrane according to claim 1, which has a N2 permeability of 1000 GPU or more at a differential pressure of 100 kPa.

3. The separation membrane according to claim 1 or 2, wherein The film surface having the layered crystal surface layer has a crystallinity of 5% to 35%.

4. The separation membrane according to any one of claims 1 to 3, wherein The area ratio of the lamellar crystals on the film surface having the surface layer of the lamellar crystals is 10% to 60% when the area of ​​the film surface excluding the openings is 100%.

5. The separation membrane according to any one of claims 1 to 4, wherein The period of the lamellar crystals on the surface of the film having the surface layer of the lamellar crystals is 10 nm to 80 nm.

6. The separation membrane according to any one of claims 1 to 5, wherein In the surface layer having the layered crystals, the micropores are 1 / μm 2 Above and 20000 / μm 2 the following.

7. The separation membrane according to any one of claims 1 to 6, wherein The porosity of the separation membrane is 30% to 70%.

8. The separation membrane according to any one of claims 1 to 7, wherein In the inner layer of the separation membrane, the porosity is 25% to 60% when the cross-sectional area when cut in the thickness direction is set to 100%.

9. The separation membrane according to any one of claims 1 to 8, wherein The separation membrane is in the shape of a hollow fiber.

10. The separation membrane according to claim 9, wherein The surface layer having the lamellar crystals is the outer surface of the separation membrane in the shape of a hollow fiber.

11. The separation membrane according to claim 9 or 10, wherein In a cross section obtained by cutting the inner layer of the hollow fiber separation membrane parallel to the longitudinal direction of the membrane and parallel to the thickness direction of the membrane, a ratio a / b of the major axis length a to the minor axis length b of the pores is 1.0 to 5.

0.

12. The separation membrane according to any one of claims 1 to 11, wherein After the separation membrane is immersed in the following organic solvent A for 3 seconds, the N2 permeability at a differential pressure of 100 kPa is 5 GPU or more. Organic solvent A: chloroform / isopropanol = 1 / 1 (volume / volume).

13. A degassing module comprising the separation membrane according to any one of claims 1 to 12.

14. A method for producing a separation membrane, comprising the steps (A1) to (A2) below: (A1) a preparation step of melt-kneading a mixture containing 10% to 50% by mass of poly(4-methyl-1-pentene) and 50% to 90% by mass of a plasticizer to obtain a resin composition; (A2) Molding process: The resin composition is discharged from a discharge die, passed through an idle run of 10 mm to 30 mm, and immediately introduced into a cooling bath of a solvent having a solubility parameter distance Ra of 4.0 to 14.0 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 3.0 to 6.0 relative to the plasticizer, to obtain a resin molded product.

15. The method for producing a separation membrane according to claim 14, wherein: After the molding step (A2) of obtaining a resin molded product, the method further includes a cleaning step (A3), in which the resin molded product is treated with a solvent having a solubility parameter distance Ra in the range of 8 to 35 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb in the range of 5 to 35 relative to the plasticizer, and the plasticizer contained in the resin molded product is extracted into the solvent.

16. The method for producing a separation membrane according to claim 15, wherein: In the (A3) washing step, the resin molded product is stretched to 1.1 to 5.0 times.

17. A method for producing a separation membrane, comprising the steps (B1) to (B3) described below, wherein in the washing step of step (B3), the resin molded article is stretched to 1.1 to 5.0 times, (B1) a preparation step of melt-kneading a mixture containing 10% to 50% by mass of poly(4-methyl-1-pentene) and 50% to 90% by mass of a plasticizer to obtain a resin composition; (B2) a molding step of immediately introducing the resin composition into a cooling bath of a solvent having a solubility parameter distance Ra of 5.0 to 18.0 with respect to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 1.0 to 2.9 or 6.5 to 10.0 with respect to the plasticizer after the resin composition is discharged from the discharge port die, to obtain a resin molded product; (B3) Cleaning step: The obtained resin molded product is treated with a solvent having a solubility parameter distance Ra of 8 to 35 relative to poly(4-methyl-1-pentene) and a solubility parameter distance Rb of 5 to 35 relative to the plasticizer, thereby extracting the plasticizer contained in the resin molded product into the solvent.

Citation Information

Patent Citations

  • Piano hammer

    JP1979013317A

  • Hollow fiber inhomogeneous membrane and its production

    JP1994210146A

  • Manufacture of hollow fiber dual membrane

    JP1995116483A

  • Method for producing an integrally asymmetrical polyolefin membrane

    WO2000043113A1